And yet it Moves: The Agenda against Inequalities in the G7 and G20. Issue 2 (14th February 2019) - Martelli, Simone; Bartolomucci, Lawrence
Abstract: Over the last years, inequality has climbed on top of the political agenda both in the G7 and G20, also as a response to the wide discontent against governments' policies. However, discussions have developed along significantly different patterns. On one hand, the G7 managed to develop a joint understanding on the main drivers and on the domestic and global policies to tackle the multiple dimensions of inequality, with no country‐specific commitment. On the other hand, G20 countries have taken up domestic policy commitments for greater inclusiveness, but they did not accomplish agreement on any common framework. Indeed, works can be further developed in both fora; however, the development of a multilateral policy‐ oriented framework on inequalities and inclusiveness in the G20 appears more pressing. Looking also at the G7 experience, this would require putting inclusive growth on top of the G20 Presidencies' work plans, ensure a stronger political engagement by all members and tackle some of the persistent flaws in the G20 governance. Abstract : The next G20 Presidencies will need to demonstrate a greater capacity in setting the agenda, putting inclusive growth on top of their work plans, rather than making it ancillary to other priorities.